The Reflection of the Plotinus reason in Masnawi Mam u Zin - Rashid, Jihad Sh. (Humanities Journal of University of Zakho, 2019)
Ahmadi Khani is one of the sophists who deduced from the art of poem and story narration. Masnawi Mam u Zin considered to be one of the most important Romantic poems in comparison with the other Romantic poems in Kurdish literature, because in addition of its romantic side it emphasized on the mystic and philosophical behavior which are the core of this poem. The realization of Khani ‘s universal philosophy is the purpose of this research ; the perspective world of Khani will be more clear and obvious for the reader in addition to that it shows to a degree the Plotinus ideas which were involved in his writings. Thinking in the invisible ideas of Mam u zin shows Khani’s creativity in using metaphor for explaining these unclear angles of the invisible ideas to reach to the wanted point in the same way of an ontologist. This research paper is written to explain the roots of reason and the world perspective of Khani in the Plotinus reason, from this perspective this research tries by the practical method analyzing the universal characteristics of Plotinus and Khani’s ontology.